Implementation and Evaluation of A Community-Based Learning Model in Islamic Education - Aris Aris; Suteja Suteja; Widodo Winarso (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
Formal Islamic education is mostly accomplished with a cognitive verbalistic approach, focused on mastering fragmental conceptual knowledge with the context of its practical application. This phenomenon occurs because many students are not involved in community activities, even though religious education needs inherent guidance and supervision from family and adults in their surrounding environment. Therefore, this study aims to analyze the impact of community-based religious learning in improving student learning outcomes. Data were collected by observing learning practices at schools, mosques/musholla, and majlis ta'lim (recitation) around students' residences. Interviews were conducted with Islamic Education teachers, while documentation studies were carried out on the assessment of test and non-test results. The results showed that community involvement specifically aims to provide awareness to parents and the wider community to actively participate in the learning process within the limits of their respective powers. Community involvement in these activities is welcomed and seen as a valuable acknowledgment of their participation. Community empowerment has become a complementary solution, hence, learning outcomes tend to increase. Further studies should be carried out with a contextual and comprehensive approach